2009
DOI: 10.1002/jcc.21327
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of magnetoresponsive aromatic and antiaromatic zones in three‐membered rings of d‐ and f‐block elements

Abstract: Magnetoresponsive three-membered rings of d- and f-block elements have been thoroughly investigated with the help of electronic structure calculation methods. The magnetic response of the clusters was evaluated by the Nucleus Independent Chemical Shifts (NICS)(zz)-scan curves, which in conjunction with symmetry-based selection rules for the most significant translationally and rotationally allowed transitions helped rationalize and predict the orbital-type of aromaticity/antiaromaticity of the clusters. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…In addition, Tsipis has recently analyzed NICS zz profiles in several organic and inorganic compounds cages [115] as well as in lanthanide three-membered rings [116].…”
Section: IIImentioning
confidence: 99%
“…In addition, Tsipis has recently analyzed NICS zz profiles in several organic and inorganic compounds cages [115] as well as in lanthanide three-membered rings [116].…”
Section: IIImentioning
confidence: 99%
“…Finally, the recently developed Anisotropy of the Current Induced Density (ACID) mapping was suggested as a better probe of aromaticity [42,43]. Recently, we showed that the NICS zz -scan curves in conjunction with symmetry-based selection rules for the lowest translationally-and rotationally-allowed transitions help rationalize and predict the orbital-type of aromaticity/antiaromaticity in magnetoresponsive three-membered rings of d-and fblock elements [44], and unequivocally probe the antiaromaticity in a wide range of antiaromatic organic and inorganic rings/cages [45]. Therefore, we thought it would be advisable to test the efficiency of the NICS zz -scan profiles in conjunction with symmetry-based selection rules to provide a clear picture of the orbital type (s-, p-, d-, f-orbital) of aromaticity in a wide range of aromatic organic and inorganic molecules, proving its general use as a powerful diagnostic tool of the orbital type of aromaticity/antiaromaticity.…”
Section: Introductionmentioning
confidence: 99%
“…34,[56][57][58][59] Heine et al 92,93 showed that the NICS zz component is directly connected to z-component of the induced magnetic field, which is the vector field originally proposed by Pople to understand aromaticity. 94 The NICS zz -scan profiles of the [c-Ln 3 ] (Ln 5 La, Ce, Pr, Nd, Gd, Lu) clusters are shown in Figure 2, while the most salient features of the NICS zz -scan curves along with the magnetic anisotropy, Dv m are compiled in Figure 4, while the most salient features of the NICS zz -scan curves are compiled in Figure 6, while the most salient features of the NICS zz -scan curves are compiled in intensively investigated.…”
Section: Resultsmentioning
confidence: 97%
“…In this work, the magnetic response of the clusters was evaluated by the NICS zz -scan curves, which in conjunction with symmetry-based selection rules for the most significant translationally (T x,y ) and rotationally (R z ) allowed transitions help rationalize and predict the orbital-type of aromaticity/antiaromaticity of the clusters. 34,[56][57][58][59] Magnetic susceptibilities were computed by the Continuous Set of Gauge Transformations method, [87][88][89] as implemented in the GAUSSIAN03 series of programs 67 using the B3LYP/STRSC level of theory. Table 2.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation